Correlation of Intelligent Quotient, Emotional Quotient, and Adversity Quotient to Badminton Athletes’ Achievement (Journal of Physical Education and Sports, 2022)
The background of this research is the difference of Intelligent Quotient, Emotional Quotient, and Adversity Quotient of badminton athletes in Semarang City on the achievements produced by athletes. The purpose of this study is to analyze and examine the interaction of Intelligent Quotient (IQ), Emotional Quotient (EQ), and Adversity Quotient (AQ) on the achievement results of badminton athletes in Semarang city. Correlational research design with cluster purposive sample technique. The instrument used by IQ is the Wonderlic Personnel Test (WPT) test. Questionnaire instruments were used to test EQ and AQ. The total subjects of this study were 71 badminton athletes in Semarang City, with the average age of 13.72 ± 0.959 years. The results showed that the results of the regression test for each variable obtained t-count IQ of 4.310, t-count EQ of 5.912, t-count AQ of 5.250 and sig all variable of <0.001. Adversity intelligence has no significant effect on the achievement of badminton athletes.. The conclusion of this study is that Intelligent Quotient, Emotional Quotient, and Adversity Quotient have a significant correlation to the achievement of badminton athletes.